A Study of Students' Engagement and Students' Speaking Skill: A Correlational Research - Febriyantina Istiara; Tommy Hastomo; Wibisana Ahmad Indriyanta (Universitas Teknokrat Indonesia, 2023)
Students' active engagement institutes the fundamental of the procedure of learning and teaching in the student-centered classroom. The objective of this research aimed to investigate the correlation between students' engagement and speaking skills in the eighth grade of SMP Negeri 18 Krui in the Academic Year of 2021/2022. The researchers used a quantitative approach as the research design in this study. The eighth-grade students of SMP Negeri 18 Krui were the population in this research, consisting of 26 students as a research sample. The researchers employed a purposive sampling technique for determining the research sample. The data on students' engagement was collected using the questionnaire, which was adapted from (Appleton et al., 2006), and the data on speaking skills were collected using the speaking test. In addition, the researchers employed a speaking test and questionnaire to collect the data. After collecting the data of the research, the researchers found that there were 20 students (77%) who had a high engagement in a learning activity with a mean score of 69.61, and there were 24 students (94%) who had fairly good in speaking skill with mean score 64.04. The findings also showed that the coefficient correlation was 0.680. Therefore, the correlation was quite high, and the researchers concluded that there was a correlation between Students' Engagement and Speaking Skills at the Eight Grade of SMPN 18 Krui in the Academic Year of 2021/2022